The use of information for diabetes research and care: patient views in West London. (20th April 2016) - Zalin, A; Papoutsi, C; Shotliff, K; Majeed, A; Marston, C; Reed, J
Abstract: Data obtained during the care of people with diabetes mellitus may be used to advance research, improve quality, encourage innovation and support better self‐care. However, the perspective of people living with diabetes is less well understood. This study examines the views of people with diabetes regarding access to electronic health records (EHRs) for health care and research. Survey data from a sub‐group of 404 individuals with diabetes were analysed from a dataset of 5331 West London participants randomly sampled in a cross‐sectional survey. These findings were explored in more detail in a focus group discussion involving people with diabetes. Sixty‐seven percent of people with diabetes would support the inclusion of their full records on a national EHR for purposes of personal health provision. The vast majority (91%) would prefer to have access to their own full medical history rather than a truncated version. Seventy‐nine percent said they would allow their EHR to be used for research: 51% allowing their records to be shared without identifiers and 28% being supportive of access to their identifiable information. A number of themes emerged from the focus group discussion on integrated EHRs, including expectations for improved communication with health professionals, increased participation in the consultation process, responsibility for self‐care and data sharing for the greater good. In conclusion, wider sharing of health information may address some of the challenges diabetes care entails, although striking a balance between information fragmentation and sharing remains crucial to improve health, research and quality outcomes. Copyright © 2016 John Wiley & Sons.